A New High Voltage Gain Transformer-Less Step-Up DC-DC Converter With Double Duty-Cycles: Design and Analysis - Imanlou, Arash; Behkam, Reza; Nadermohammadi, Ali; Nafisi, Hamed; Heydari-Doostabad, Hamed; Gharehpetian, Gevork B. (IEEE access, 2024)
This paper proposes a new high gain step-up non-isolated transformer-less DC-DC converter, achieved through the effective integration of an active switched-inductor network with switched-capacitors. A substantially high voltage gain is achieved considering the quantity of components employed in its structure. Benefiting from double duty cycles, a notable attribute of the propounded circuit is its capability to obtain a consistent voltage gain through diverse duty cycle configurations. The second duty cycle introduces an additional degree of freedom to both the design procedure and the converter control system design. The pole placement control method is employed to regulate the converter, controlling both duty cycles simultaneously. The attainment of a high voltage gain, such as a gain of 20, is feasible through the use of low duty cycle values ( D_{1}=50 % and D_{2}=35 %). Also, the power switches are subject to less voltage stresses ( V_{S1}=V_{S2}= 0.26V_{out} and V_{S3}= 0.48V_{out} ), enabling the implementation of low voltage rating MOSFETs with low on-resistance, resulting in improved efficiency. Moreover, the output switch under zero-voltage switching (ZVS) conditions and low turn-off switching losses of the input switches lead to an increased efficiency. Omitting the use of a transformer or coupled-inductors in this design reduces the converter size and weight, eliminates the challenges of leakage inductors, and also simplifies analysis, design, and fabrication procedure. The operation principles, steady-state analysis, design considerations, and efficiency calculations are provided in detail, followed by dynamic modeling and control analysis. To assess the merits of the propounded converter, a comparison study is conducted against those of other relevant converters. Ultimately, for the purpose of validating the suggested design, the converter simulation model in PSIM software is tested, and a 300W laboratory prototype is fabricated and evaluated.